Identification of age differences in cancer-related symptoms in women undergoing chemotherapy for breast cancer in China - Tingting Cai; Tingting Zhou; Jialin Chen; Qingmei Huang; Changrong Yuan; Fulei Wu (BMC, 2023)
Abstract Background Both contextual and cancer-related factors could be identified as causes of the interindividual variability observed for symptoms experienced during breast cancer treatment with chemotherapy. Understanding age differences and the predictors of latent class memberships for symptom heterogeneity could contribute to personalized interventions. This study aimed to identify the role of age differences on cancer-related symptoms in women undergoing chemotherapy for breast cancer in China. Methods A cross‑sectional survey was conducted among patients with breast cancer in three tertiary hospitals in central China between August 2020 to December 2021. The outcomes of this study included sociodemographic and clinical characteristics, Patient-Reported Outcomes Measurement Information System (PROMIS)-57 and PROMIS-cognitive function short form scores. Results A total of 761 patients were included, with a mean age of 48.5 (SD = 11.8). Similar scores were observed across age groups for all symptoms except for fatigue and sleep disturbance domains. The most central symptoms varied among each group, and were fatigue, depression, and pain interference for the young-aged, middle-aged, and elderly-aged groups, respectively. In the young-aged group, patients without health insurance (OR = 0.30, P = 0.048) and in the fourth round of chemotherapy or above (OR = 0.33, P = 0.005) were more likely to belong to low symptom classes. In the middle-aged group, patients in menopause (OR = 3.58, P = 0.001) were more likely to belong to high symptom classes. In the elderly-aged group, patients with complications (OR = 7.40, P = 0.003) tended to belong to the high anxiety, depression, and pain interference classes. Conclusions Findings from this study indicated that there is age-specific heterogeneity of symptoms present for Chinese women being treated for breast cancer with chemotherapy. Tailored intervention should consider the impact of age to reduce patients' symptom burdens.